Reversion of MRAP2 Protein Sequence Generates a Functional Novel Pharmacological Modulator for MC4R Signaling - Jing Xu; Meng Wang; Yanbin Fu; Cong Zhang; Zhe Kuang; Shan Bian; Rui Wan; Shen Qu; Chao Zhang (Biology, 2022)
As a member of the melanocortin receptor family, melanocortin 4 receptor (MC4R) plays a critical role in regulating energy homeostasis and feeding behavior, and has been proven as a promising therapeutic target for treating severe obesity syndrome. Numerous studies have demonstrated that central MC4R signaling is significantly affected by melanocortin receptor accessory protein 2 (MRAP2) in humans, mice and zebrafish. MRAP2 proteins exist as parallel or antiparallel dimers on the plasma membrane, but the structural insight of dual orientations with the pharmacological profiles has not yet been fully studied. Investigation and optimization of the conformational topology of MRAP2 are critical for the development of transmembrane allosteric modulators to treat MC4R-associated disorders. In this study, we synthesized a brand new single transmembrane protein by reversing wild-type mouse and zebrafish MRAP2 sequences and examined their dimerization, interaction and pharmacological activities on mouse and zebrafish MC4R signaling. We showed that the reversed zebrafish MRAPa exhibited an opposite function on modulating zMC4R signaling and the reversed mouse MRAP2 lost the capability for regulating MC4R trafficking but exhibited a novel function for cAMP cascades, despite proper expression and folding. Taken together, our results provided new biochemical insights on the oligomeric states and membrane orientations of MRAP2 proteins, as well as its pharmacological assistance for modulating MC4R signaling.